\[\boxed{\text{1207\ (1207).}\text{\ }\text{Еуроки\ -\ ДЗ\ без\ мороки}}\]
\[при\ n = 3k:\ \]
\[n^{3} + 2n = 27k^{3} + 6k =\]
\[= 3 \cdot \left( 9k^{3} + 2k \right) - делится\ на\ 3.\]
\[при\ n = 3k + 1:\ \ \]
\[(3k + 1)^{3} + 2 \cdot (3k + 1) =\]
\[= 27k^{3} + 27k^{2} + 9k + 1 + 6k + 2 =\]
\[= 27k^{3} + 27k^{2} + 15k + 3 =\]
\[= 3 \cdot \left( 9k^{3} + 9k^{2} + 5k + 1 \right) -\]
\[делится\ на\ 3.\]
\[при\ n = 3k + 2:\]
\[(3k + 2)^{3} + 2 \cdot (3k + 2) =\]
\[= 27k^{3} + 54k^{2} + 36k + 8 + 6k + 4 =\]
\[= 27k^{3} + 54k^{2} + 42k + 12 =\]
\[= 3 \cdot \left( 9k^{3} + 18k^{2} + 14k + 4 \right) -\]
\[делится\ на\ 3.\]
\[Ответ:можно.\ \]
\[\boxed{\text{1207.}\text{\ }\text{Еуроки\ -\ ДЗ\ без\ мороки}}\]
\[1)\ 2^{36} + 4^{100} - 2^{32} - 4^{98} =\]
\[= 2^{36} + \left( 2^{2} \right)^{100} - 2^{32} - \left( 2^{2} \right)^{98} =\]
\[= 2^{36} + 2^{200} - 2^{32} - 2^{196} =\]
\[= \left( 2^{36} - 2^{32} \right) + \left( 2^{200} - 2^{196} \right) =\]
\[= 2^{32} \cdot \left( 2^{4} - 1 \right) + 2^{196} \cdot \left( 2^{4} - 1 \right) =\]
\[= \left( 2^{4} - 1 \right)\left( 2^{32} + 2^{196} \right) =\]
\[= (16 - 1)\left( 2^{32} + 2^{196} \right) =\]
\[= 15 \cdot \left( 2^{32} + 2^{196} \right) - кратно\ 15.\]
\[2)\ 2^{36} + 4^{100} - 2^{32} - 4^{98} =\]
\[= 2^{36} + \left( 2^{2} \right)^{100} - 2^{31} - \left( 2^{2} \right)^{98} =\]
\[= 2^{36} + 2^{200} - 2^{32} - 2^{196} =\]
\[= \left( 2^{36} - 2^{32} \right) + \left( 2^{200} - 2^{196} \right) =\]
\[= 2^{32} \cdot \left( 2^{4} - 1 \right) + 2^{196} \cdot \left( 2^{4} - 1 \right) =\]
\[= \left( 2^{4} - 1 \right)\left( 2^{32} + 2^{196} \right) =\]
\[= 15 \cdot \left( 2^{32} + 2^{196} \right) =\]
\[= 15 \cdot 2^{4} \cdot \left( 2^{28} + 2^{192} \right) =\]
\[= 15 \cdot 16 \cdot \left( 2^{28} + 2^{192} \right) =\]
\[= 240 \cdot \left( 2^{28} + 2^{192} \right) -\]
\[кратно\ 240.\ \]